Perilaku Zero Waste Dan Dampaknya Pada Keberlanjutan Lingkungan di Indonesia - Pratiwi, Nur (Balitbangda Provinsi Jambi, 2023)
The growing behavior of consumerism has proven to be significant in contributing to waste that damages ecosystems. However, recently there has been groups of people who adopted zero waste behavior in order to reduced waste. The zero waste concept originally come from companies awareness regarding their waste disposal, but over the years this concepts has been reached out to the household level. Using qualitative approach, this study combined in-depth interview and observation as data collection methods to explore the role of local wisdom and ecological awareness in shaping zero waste behavior and follow up questions regarding social learning theory. The study involved 10 informants. They are varied on the basis of age, gender, and income. The study indicates that the concept of zero waste is a derivative concept of voluntary simplicity that has existed since the 1950s and developed as a concept that initially used by companies as their disposal waste method then developed as behavior adapted by households. Zero waste behavior is important for circular economy, Local wisdom, ecological awareness, health awareness, income, and access to information are various aspects that influence the formation of zero waste behavior.